Cigarette Taxes and Teen Marijuana Use - D. Mark Anderson; Kyutaro Matsuzawa; Joseph J. Sabia (Institute of Labor Economics (IZA), 2020)
The spillover effect of cigarette taxes on youth marijuana use has been the subject of intense public debate. Opponents of cigarette taxes warn that tax hikes will cause youths to substitute toward marijuana. On the other hand, public health experts often claim that because tobacco is a "gateway" drug, higher cigarette taxes will deter youth marijuana use. Using data from the National and State Youth Risk Behavior Surveys (YRBS) for the period 1991-2017, we explore the relationship between state excise taxes on cigarettes and teen marijuana use. In general, our results fail to support either of the above hypotheses. Rather, we find little evidence to suggest that teen marijuana use is sensitive to changes in the state cigarette tax. This null result holds for the sample period where cigarette taxes are observed to have the largest effect on teen cigarette use and across a number of demographic groups in the data. Finally, we find preliminary evidence that the recent adoption of state e-cigarette taxes is associated with a reduction in youth marijuana use.
Keywords: I12; I18; K42; 330; cigarette taxes; teen marijuana use; e-cigarette taxes; youth risky behavior